2019
DOI: 10.1093/infdis/jiy743
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cross-reactivity Against Nonvaccine Human Papillomavirus Types 31 and 45 After 2- or 3-Dose Schedules of the AS04-Adjuvanted Human HPV-16/18 Vaccine

Abstract: This analysis focused on long-term cross-reactive immunogenicity against nonvaccine human papillomavirus (HPV) types 31 and 45 following 2 doses of AS04-adjuvanted HPV-16/18 vaccine in girls aged 9–14 years or following 3 doses in women aged 15–25 years, for up to 3 years (HPV-070 study) and up to 5 years (HPV-048 study) after the first vaccination. Both schedules elicited antibodies against HPV-31 and HPV-45 up to 5 years after first dose. The antibody concentration was similar in young girls as compared to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Therefore, the concept of established infection could potentially be applied to each HPV genotype. Furthermore, available HPV vaccines are safe and tolerable [18–20] and a persistent cross-reactive immune response against HR-HPV not covered by the vaccine was shown in vaccinated women [21]. However, vaccination has a clinically relevant role also in subjects with established HPV infection [13, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the concept of established infection could potentially be applied to each HPV genotype. Furthermore, available HPV vaccines are safe and tolerable [18–20] and a persistent cross-reactive immune response against HR-HPV not covered by the vaccine was shown in vaccinated women [21]. However, vaccination has a clinically relevant role also in subjects with established HPV infection [13, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported cross-NAbs to HPV31 and 45, one month following two or three doses of 2vHPV or 4vHPV immunisation, at approximately 100-fold lower levels than vaccine-type NAb [16][17][18][19]. These cross-NAbs were found to persist for at least 5 and 2 years for 2vHPV and 4vHPV, respectively [16,17,25,26]. Our data extends these observations for HPV31 to six years (approximately 100-fold lower levels than vaccine-type NAb observed previously [22]), as well as to girls who received two doses of 4vHPV, suggesting that two doses given to girls under 15 years old may be sufficient to induce cross-protection to HPV31 in the long-term.…”
Section: Discussionmentioning
confidence: 92%
“…For the 2vHPV vaccine, similar antibody concentrations against HPV31 and HPV45 were measured up to 5 y after both two and three doses of vaccination. 72 For the 4vHPV vaccine, higher antibody concentrations against HPV31 were observed up to 6 y after one-, two-, or three-dose-vaccination as compared to no vaccination, but this was not observed for other cross-protective serotypes. 82 This difference in antibody response against cross-protective types between vaccines might be due to the AS04 adjuvant system used in the 2vHPV vaccine, which is claimed to induce a broader immune response and may hence lead to higher antibody levels.…”
Section: Immune Responses Following Fewer Than Three Doses Of Hpv Vac...mentioning
confidence: 85%
“…Again, this level of cross-protection was higher for the 2vHPV compared to the 4vHPV vaccine. 72 Generally speaking, although cell-mediated immune effectors provide information on the responsiveness to the vaccine, they do not directly indicate how well the vaccine protects or how long antibodies are maintained (which is due to the production by LLPCs). 22 Nevertheless, further research on the long-term persistence of memory B- and T-cells could provide an indication for the sustainability of protection from disease, as is the case in hepatitis B studies.…”
Section: Long-term Immune Responses Following Three Doses Of Hpv Vacc...mentioning
confidence: 99%